Prognostic factors of diabetic retinopathy among adult patients with type ii diabetes mellitus in Kelantan from 2013 to 2017 - Samsuri, Muhammad Za’im Mohd (2024)
Introduction: Diabetic Retinopathy (DR), a common and severe complication of diabetes, is a leading cause of blindness and significantly affects quality of life. In Kelantan, the high prevalence of diabetes and the substantial proportion of patients with DR highlight a critical public health challenge. This study aims to determine the event probability of DR and identify its prognostic factors among adult patients with type II diabetes mellitus (T2DM) in Kelantan from 2013-2017. Methodology: A retrospective cohort study was conducted in Kelantan among adult patients with type II diabetes mellitus (T2DM) registered in the National Diabetic Registry (NDR) from 1st January 2013 to 31st December 2017. Simple random sampling was used to select the cases. Survival analysis was used to examine time to diabetic retinopathy. The Cox Proportional-Hazards Regression Model is used to analyse prognostic factors. Results: In the final analysis of 1372 adult patients with T2DM, 11.9% developed DR over the study duration, with an increasing trend over five years (reaching 9.5% by the fifth year). Significant prognostic factors for DR progression were age, hypertension, nephropathy, HbA1c levels, and triglyceride (TG) levels. Patients aged 60 or older exhibited a significantly higher hazard of developing DR compared to those under 60 years old (Adj. HR: 1.85; 95% CI:1.30, 2.62). Those with nephropathy were at a substantially increased hazard of DR compared to those without nephropathy (Adj. HR: 3.46; 95% CI: 2.41, 4.97). Patients with HbA1c levels of 6.5 and above were more likely to develop DR than those with levels below 6.5 (Adj. HR: 1.42; 95% CI: 1.01, 2.02). An increase in TG levels was associated with a higher hazard of progression to DR (Adj. HR: 1.18; 95% CI: 1.03, 1.34). Those with hypertension had a decreased hazard of developing DR compared to those without hypertension (Adj. HR: 0.33; 95% CI: 0.24, 0.47). Conclusion: Our study reveals a significant increase in DR prevalence with longer durations of diabetes mellitus. We identified older age, nephropathy, elevated HbA1c, and high TG levels as prognostic factors for DR in T2DM patients, while hypertension surprisingly showed a protective effect. These findings highlight the importance of risk factor identification for targeted prevention strategies, potentially improving patient management and quality of life by mitigating DR incidence and severity in T2DM.